5.5 mm implant. A solution for severe atrophies without sacrificing predictability - Anitua, Eduardo (2022)
The rehabilitation of areas of the maxilla and mandible with extreme resorption is a fact of increased presence in our dental practice. Surgical techniques such as short and extra-short implants facilitate the resolution of these clinical cases. In this clinical case report we develop a case rehabilitated using a 5.5 mm long implant and we provide a biomechanical study of the behaviour of implants with these characteristics.